Tata Kelola Keuangan Keluarga Pada Ibu Rumah Tangga Pemilik UMKM DI Desa Banjarsari, Cerme, Gresik - Aji Prasetyo; Nurdina; I Made Bagus Dwiarta; Nashrudin Latif; Silviana Anggraini Ardya Putri; Indah Ayu Avilia (Ekobis Abdimas, 2022)
Government policies such as Work Form Home (WFH), social distancing, and Large-Scale Social Restrictions (PSBB) in the last two years have still had an impact on reducing people's purchasing power. One of the disadvantaged sectors is MSME. This service aims to provide financial governance assistance as an effort to control and control family finances for housewives who own MSMEs in Banjarsari Village. The role of housewives who own MSMEs is vital in managing the family economy. The key to family success is how to manage family finances well. This service uses the workshop method by applying the preparation of financial reports using simple accounting. Participants in this activity were 25 people who were then assisted in preparing simple finances. Where this service produces simple bookkeeping that describes the finances of each MSME in Banjarsari Village as a form of careful implementation of financial control and control. Knowledge and soft skills regarding family financial management for housewives who own MSMEs are needed to manage the family economy and their business ventures.